2018
DOI: 10.1002/chem.201804416
|View full text |Cite
|
Sign up to set email alerts
|

Reengineering Chemical Glycosylation: Direct, Metal‐Free Anomeric O‐Arylation of Unactivated Carbohydrates

Abstract: To sustain innovation in glycobiology, effective routes to well-defined carbohydrate probes must be developed. For over a century, glycosylation has been dominated by the formation of the anomeric Csp -O acetal junction in glycostructures. A dissociative mechanistic spectrum spanning S 1 and S 2 is frequently operational thereby reducing the efficiency. By reengineering this fundamental process, an orthogonal disconnection allows the acetal to be formed directly from the reducing sugar without the need for sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…A recent example by the Gilmour group allowing glycosidation of a 2,2difluorinated reducing sugar appears very promising. 521 Establishing efficient protocols to employ polyfluorinated sugar donors in an automated glycan synthesis setting will be another key advancement. It is worth pointing out that enzymatic glycosyl formation with polyfluorinated donors has not yet been achieved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent example by the Gilmour group allowing glycosidation of a 2,2difluorinated reducing sugar appears very promising. 521 Establishing efficient protocols to employ polyfluorinated sugar donors in an automated glycan synthesis setting will be another key advancement. It is worth pointing out that enzymatic glycosyl formation with polyfluorinated donors has not yet been achieved.…”
Section: Discussionmentioning
confidence: 99%
“…The modification of glycosyl donor reactivities by polyfluorination is naturally even more pronounced than with monofluorinated sugars, and perhaps the development of other methodologies than the traditional acid-catalyzed/electrophile-induced or base-mediated anomeric glycosidation will provide extra opportunities. A recent example by the Gilmour group allowing glycosidation of a 2,2-difluorinated reducing sugar appears very promising . Establishing efficient protocols to employ polyfluorinated sugar donors in an automated glycan synthesis setting will be another key advancement.…”
Section: Discussionmentioning
confidence: 99%
“…Further, to evaluate the stability of acid‐sensitive protecting groups, like benzylidene, trityl, and tert ‐butyldimethylsilyl, benzyl glycosides 22 , [10] 24 [10] and 26 were synthesized and subjected to the above regioselective anomeric debenzylation reaction conditions. Again, it was shown that these protective groups are stable, and the only products isolated were the corresponding hemiacetals 23 , [19] 25 [10] and 27 , respectively, in good yield ((Table 2, entries 6–8). These results show that the OTBS, OAc, benzylidene acetal, and trityl protecting groups were stable under the present regioselective anomeric benzyl deprotection reaction conditions [20]…”
Section: Methodsmentioning
confidence: 98%
“…(15). 8,69 The compound was synthesized from commercially available lactose (11) using the same procedure as 7. White powder (Final yield of 15 from 1.43 g, 3.2 mmol of 14 = 2.2 g, 64%).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%